Estrategia internacional de las empresas japonesas en los países del sudeste asiático y China - Oizumi, YOICHI; Muñoz, Félix-Fernando; Encinar, María Isabel (Papeles del Este, 2007)
The Asian market is not merely a factory with low wages. It is also a consumer market with a huge potential for growth, in which there exists high technology and qualified workers. This paper explores the trends of Japanese manufacture firms in their expansion in South East countries and China. The big magnitude of these markets is a key point in their international strategies.